Chemical constituents from Hibiscus hamabo and their antiphotoaging effects on UVA‐induced CCD‐986sk. (6th March 2022) - Park, Gwee Kyo; Jang, Wookju; Kim, Bo Yun; Oh, Kyung‐Eon; Kim, You Ah.; Kwon, Hyuk Joon; Kim, Soo‐Young; Park, Byoung Jun
Abstract: To investigate the phytochemical constituents of Hibiscus hamabo, a chromatographic method was used. A new phenolic glucoside, woodorien A (1 ), along with 10 known compounds, rutin (2 ), isoquercetin (3 ), nicotiflorin (4 ), astragalin (5 ), trans ‐tiliroside (6 ), N ‐ trans ‐feruloyltyramine (7 ), N ‐ trans ‐caffeoyltyramine (8 ), woodorien (9 ), quercetin 3′‐galactopyranoside (10 ), and cis ‐tiliroside (11 ), was isolated. The structure of 1 was identified as ethyl 3‐O‐ β ‐d ‐glucopyranosyl‐4‐hydroxybenzoate. Compounds 8, 9, and 11 were isolated from genus Hibiscus, and 2 –7 and 10 were isolated from H. hamabo for the first time. Their chemical structures were determined through the interpretation of spectroscopic data. The properties of the UVA photoaging induction assay of all isolated compounds were measured. Compounds 3, 8, and 10 exhibited recovery from photoaging induced by UVA in CCD‐986sk. These results suggest that H. hamabo is a potential source of natural antiphotoaging ingredients and can be used in cosmetic applications. Abstract : A new compound, woodorien A (1 ), together with 10 known compounds (2 –11 ) was isolated from Hibiscus hamabo via chromatography. Their chemical structures were elucidated on the basis of spectroscopic methods. Among these, compounds 8, 9, and 11 were reported from genus Hibiscus, and 2 –7 and 10 were reported from H. hamabo for the first time. All isolated compounds 1 –11 were tested by a UVA photoaging induction assay. As a result, isoquercetin (3 ), N ‐ trans ‐caffeoyltyramine (8 ), and quercetin 3′‐galactopyranoside (10 ) showed strong antiphotoaging activity.